Almost Menger property in bitopological spaces - Eysen, A. F.; Özçağ, E. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We introduce the notion of almost Menger property in bitopological spaces. We give some characterizations in terms of (i, j)-regular open sets and almost continuous surjection. We also investigate the notion of almost γ -set in the bitopological context.